STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI GURU DI RAUDHATUL ATFHAL WACHID HASYIM KOTA BATU - Eni Hendrawati; Devi Wahyu Ertanti; Eko Setiawan (UNISMA, 2022)
To make changes to improve teacher competence, the right principal strategy is needed. This study aims to find out the principal's strategy and what obstacles are experienced by the principal in improving teacher competence and to find out the competencies possessed by teachers in RA Wachid Hasyim, Batu City. This type of research is qualitative research. Data collection techniques through observation, interviews and documentation. The subjects of this study were principals and teachers. The results showed: 1) Of the four elements of competence that must be possessed by teachers, they cannot be fully implemented properly and need to be improved again. 2) The principal plays a very important role for the progress and sustainability of the school so that the strategy carried out by the principal is in accordance with his duties. 3) The obstacles faced by the principal are internal factors are cost, time, teacher interest, and external factors are facilities and infrastructure, as well as the family environment.